The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.7717/peerj.12680
|View full text |Cite
|
Sign up to set email alerts
|

Identifying changes in immune cells and constructing prognostic models using immune-related genes in post-burn immunosuppression

Abstract: Background Burn patients are prone to infection as well as immunosuppression, which is a significant cause of death. Currently, there is a lack of prognostic biomarkers for immunosuppression in burn patients. This study was conducted to identify immune-related genes that are prognosis biomarkers in post-burn immunosuppression and potential targets for immunotherapy. Methods We downloaded the gene expression profiles and clinical data of 213 burn patients and 79 healthy samples from the Gene Expression Omnibu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…In addition, the MAPK signaling pathway also plays an important role in the process of burn injury ( 24 , 25 ). These inflammatory mediators and signaling pathways can also be targets for burn treatment ( 26 ). Burn injury causes changes in the transcriptome of 80% of leukocytes, which stimulates innate genes (pro - and anti-inflammatory cytokines) and inhibits adaptive immune responses ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the MAPK signaling pathway also plays an important role in the process of burn injury ( 24 , 25 ). These inflammatory mediators and signaling pathways can also be targets for burn treatment ( 26 ). Burn injury causes changes in the transcriptome of 80% of leukocytes, which stimulates innate genes (pro - and anti-inflammatory cytokines) and inhibits adaptive immune responses ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of key genes was associated with the percentage of Th cells (CD4+) and survival and was a good predictor of burn prognosis. 56 In addition, proteomic analysis showed that hemoglobin Subunit α 1(HBA1), Transthyretin (TTR), and Serpin Family F Member 2 (SERPINF2) correlated with mortality outcomes, and are promising markers for the future. 57 These genetic and protein expression information are mainly studies that capture changes in the acute phase and support the immune response that has been discussed above.…”
Section: Genetic Analysis Of Burn Patientsmentioning
confidence: 99%
“…Besides, preceding researches have illustrated that more than 60% of deaths in burn patients are associated with infection-related complications, primarily on account of antibiotic resistance. Immune disorder after burn is an signi cant reason of infection [3]. Therefore, screening diagnostic markers of burn immune dysfunction can be used to prevent serious complications and death.…”
Section: Introductionmentioning
confidence: 99%